(untitled) - Relethford, John (Mountain View, Calif., 1997)
Now in full color, this biological anthropology text presents balanced coverage of the major components of the field: genetics and evolutionary theory, human biological variation, primate biology and behavior, and human evolution. The relationship between biology and culture is a major focus throughout the text, and the emphasis is on the human species within the primate order: discussions of mammals and nonhuman primates continually refer back to their potential relevance for understanding the human species. The text contains material often neglected in introductory texts, such as discussions of adaptation, human health and disease and demography, and human growth.
Keywords: Physical anthropology